EVALUASI PROGRAM DESA MANDIRI ANGGUR MERAH (ANGGARAN UNTUK RAKYAT MENUJU SEJAHTERA) DI KECAMATAN LAMBOYA KABUPATEN SUMBA - Frengky Niga Awang; Retno Sunu Astuti (Magister Administrasi Publik, FISIP, 2019)
The Government's commitment to empowering the Autonomous Region to eradicatepoverty today is very beneficial to the development of a region, but the commitment mustbe coupled with the willingness of the local government concerned and appropriatepolicies. The policy of the Red Grass Village Program in the form of providing capital tothe community in the form of farmer groups in Lamboya Sub-district is a form ofgovernment commitment to eradicate poverty in the area. The problem that occurred inthe policy of Red Mandiri Anggur Village Program is that the policy does not reduce thepoverty rate, does not encourage the empowerment of village institutions, and the absenceof new entrepreneurs. The purpose of this study is to evaluate the success of the red winevillage self-service program policy by looking at Willyam Dunn's evaluation indicatorsof effectiveness, responsiveness, and accuracy. And to analyze the factors inhibiting thesuccess of Dedy Mulyadi policy that is the content of policies, implementers, andenvironment. This research uses a qualitative approach with a purposive technique todetermine key informant. The results of the evaluation indicate that the policy of MandiriAnggur Merah Village Program in Lamboya Sub-district of West Sumba Regency has notsucceeded in reducing the poverty level after the policy, unsuccessful to encourage theempowerment of village institutions and the creation of new entrepreneurs. While theobstacles to the success of the policy are the lack of clear policy content such asorganizing, the implementation of less socialized programs to the community and the lackof support from the community and government.